Determinan Kinerja Pemerintah Daerah: Ukuran Pemda, Leverage, Temuan Audit dan Tindak Lanjutnya - Kiswanto Kiswanto; Dian Fatmawati (Universitas Swadaya Gunung Jati, 2019)
This study aims to obtain empirical evidence about the effect of size, leverage, audit findings, and follow-up of audit recommendation to the local governance performance in Java Island. Local government performance is measured by scores on the evaluation of local government performance (EKPPD) derived from local government organizers report (LPPD. Population of this research is all the district/city in Java Island during 2014. According to purposive sampling method, this study employs sample of 109 local government in Java Island in 2014. Research data analysis using descriptive analysis statistical and multiple regression analysis with SPSS version 21. The result demonstrate that size and follow-up of audit recommendation have significant positive effect on the performance of local government districts/cities in Java Island. Audit findings significant negative effect on the performance of local government districts/cities in Java Island. Leverage had no significant effect to the performance of local government districts/cities in Java Island. Based on the research result can be conclude furthmore that size and follow-up of audit recommendation can increase performance of local government.Keywords: Local government performance; size; leverage; audit findings; follow-up of audit recommendation; scores of local government performance